LOCAL-CHARGED FOLKLORE IN INNOVATIVE SOLE LEARNING - Yuki, Librilianti Kurnia (IJLECR (International Journal of Language Education and Cultural Review), 2021)
This study provides an overview of SOLE learning by using innovative learning with synchronous and asynchronous and teaching techniques in local content folklore teaching material models with an essential role in higher education as MKDU for Indonesian Language and Literature Learning in one of University in Cianjur, descriptive qualitative research with content analysis. The purpose of this study is to describe SOLE, namely the learning management system asynchronously; it is essential to familiarize students with student centre learning such as SOLE is an example of independent learning that can build an independent generation because students are used to having psychological responsibility the more roles and responsibilities the more significant character that will shape the student so that he is increasingly able to regulate himself and can make his own The content as the methodology is applied to describe the folklore teaching material model with local content in the Indonesian Language and Literature Learning. So that local content folklore on the innovative Indonesian Language and Literature learning model based on SOLE types of learning with the synchronous and asynchronous techniques produces "religious" character values ​​in students that will be applied in Higher Education Cianjur.